The Effect of Applying Skimming Technique on Grade XI Students™ Reading Comprehension - Hutabarat, Benny Jefri Wijaya; Arifin, Tina Mariany (TRANSFORM: Journal of English Language Teaching and Learning, 2014)
ABSTRACT This study was conducted as an attempt to discover the effect of applying skimming technique on Grade XI students™ reading comprehension. It was an experimental research. The subject was students of Grade XI, Private Senior High School (Sekolah Menengah Atas Swasta: SMA) Methodist-7, which consisted of 60 students. The research was divided into two groups: experimental and control groups. The instrument used to collect the data was reading comprehension test. To obtain the reliability of the test, the writer applied Kuder Richardson 21 formula. The result of the reliability was 0.89. The data were analyzed by using t-test formula. The analyze showed that the scores of the students in the experimental group were significantly higher than the scores of the students in the control group at the level of significance 0.05 with the degree of freedom (df) 60 , t-observed value 3.71 > t-table value 2.00. Based on the reliability of the test, it was found that the test was reliable. The findings indicated that using Skimming Technique significantly affected the students™ reading comprehension. So, English teachers are suggested to use Skimming Technique in order to improve students™ reading comprehension.   Keywords: Skimming Technique, Reading Comprehension, Experimental Research.